The thematic representation of NASA digital images on Flickr the contributions of knowledge organization systems - Dias, Danilo Camargo [UNESP]; Moreira, Walter [UNESP]; Alves, Rachel Cristina Vesu [UNESP] (Univ Estadual Campinas - Sistema Bibliotecas, 2020)
The growth of social networks and the way of representing their resources has become the subject of several studies in Information Science (IS). The digital image carries a difficulty in relation to its thematic representation in these social networks. Thus, the problem with this study is to investigate the retrieval of information on social networks, especially on networks that make available digital images. The objective is to analyze the contributions of the Knowledge Organization System - KOS - of the National Aeronautics and Space Administration - NASA, in the thematic representation of digital images made available on Flickr's social networks. The exploratory and descriptive approach was used as methodology, which enabled the bibliographical review of theoretical aspects and the analysis of terminology in digital images at NASA's Flickr. Therefore, the terms of non-controlled thematic representation described by folksonomies, and the controlled terms from the NASA thesaurus were analyzed. As results of the analysis, the challenges generated by the use of folksonomy in the thematic representation of digital images, and the advantages of using KOS in the processes of thematic representation and information retrieval in these environments are highlighted. It is concluded that folksonomies freely represent terms and reflect the terminological reality of a community, while KOS' contribute to a control of vocabulary and more accurate information retrieval.
Keywords: Knowledge organization systems; Digital images; Folksonomy; Information retrieval